Impact of a Dietary Regimen Accompanying to Dietary supplements on Some Biochemical Indicators for Iraqi National Team Weightlifters - Mahdi, Mustafa Salih; Hadi, Ali Ahmed; Abdul-Hassan, Ghassan Adeeb (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to identify the impact of a dietary regimen accompanying to dietary supplements on some biochemical indicators for Iraqi national team weightlifters. The research problem focuses on the emergence of fatigue and muscular pain among these players, and pallor during the second phase of the training camp. Unfortunately, these symptoms have been treated incorrectly by having short period of rest, taking analgesics, and receiving massage sessions without making the medical examinations necessary for addressing the actual cause for such a fatigue or following a dietary regimen. Therefore, the researchers established a dietary regimen that encompasses four main meals throughout the preparation period. The dietary supplements include L-Carinttine (Crintine 500 mg, ISO Whey protein 100 mg, Tribulus 625 mg, Vitamin E, Branched-Chain Amino Acids [BBCA]. The researchers have determined the biochemical variables of Glutamic-pyruvic transaminase (GPT) and Glutamic-oxaloacetic transaminase (GOT) measurements, S. Alkaline phosphatase, blood urea, total bilirubin, and erythrocyte sedimentation rate (ESR). The study results revealed that the dietary regimen accompanying to dietary supplements has a positive influence on the aforementioned biochemical indicators. The researchers recommend using a dietary regimen in line with the training program.